Dynamics of Development of Oikonymic System in Northern Lyudik Language Area - I. I. Mullonen; A. Yu. Zhukov (Научный диалог)
Some aspects of the formation of the oikonymic system of the local territory during the second half of the II millennium, which is caused, on the one hand, by the development of the settlement structure, and on the other, by the laws of toponymic nomination are discussed in the article. The material for analysis was information from historical documents (cadastres, census lists, lists of populated areas) of the 16th - early 20th centuries, as well as the results of field gatherings in the territory of the northwestern Onega inhabited by Karelian people. It is proved that the system of oikonyms includes elements dating back to different chronological periods. At the same time, oikonymic models are identified that mark individual stages in the development of the system. Particular attention is paid to the existence of oikonyms on two levels: official (written) and unofficial (oral). Of these, the former was more conservative, and the latter was more responsive to changes in circumstances related to the life of the settlement, change of ownership of the courtyard, etc. It was revealed that the widespread adoption and consolidation in the official practice of popular names occurred in the middle of the XIX century. The relevance of the study lies in a number of new etymological interpretations of oikonyms, for which historical sources are used, which made it possible to build chains of successively changing variants of the name. As a result, some Karelian folk forms of Orthodox names were reconstructed, and the list of non-calendar Karelian anthroponyms was expanded.